2020
DOI: 10.1016/j.oraloncology.2020.104672
|View full text |Cite
|
Sign up to set email alerts
|

Malignant tumors of the maxillary sinus: Prognostic impact of neurovascular invasion in a series of 138 patients

Abstract: Background: Maxillary sinus cancer is a rare disease with heterogeneous biologic behavior. The pattern of neurovascular invasion is known to be an important prognosticator in head and neck cancers, but has not been studied in maxillary malignancies. Materials and methods: Patients undergoing surgery-based treatment with curative intent for a malignancy of the maxillary sinus at the Unit of Otorhinolaryngology-Head and Neck Surgery of the University of Brescia between November 2000 and October 2018 were include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 53 publications
(71 reference statements)
4
12
0
Order By: Relevance
“…This pattern of invasion brings the tumor into an area with a highly represented lymphatic network, with a consequent increased risk of lymphatic spread. This hypothesis is supported by the findings published by Ferrari et al in their series of 138 maxillary sinus cancers [ 113 ]; they found that the incidence of nodal metastasis was significantly associated with the presence of lymphovascular invasion, which, in turn, was higher when inferior structures (i.e., hard and soft palate, alveolar process, and buccinator muscle) were involved. Since the invasions of these structures configures a cT2 category but does not exclude a possible more advanced stage tumor, it seems more reasonable to suggest an elective treatment of the neck based on the inferior extension of a maxillary cancer rather than on its T category.…”
Section: Treatmentsupporting
confidence: 66%
See 1 more Smart Citation
“…This pattern of invasion brings the tumor into an area with a highly represented lymphatic network, with a consequent increased risk of lymphatic spread. This hypothesis is supported by the findings published by Ferrari et al in their series of 138 maxillary sinus cancers [ 113 ]; they found that the incidence of nodal metastasis was significantly associated with the presence of lymphovascular invasion, which, in turn, was higher when inferior structures (i.e., hard and soft palate, alveolar process, and buccinator muscle) were involved. Since the invasions of these structures configures a cT2 category but does not exclude a possible more advanced stage tumor, it seems more reasonable to suggest an elective treatment of the neck based on the inferior extension of a maxillary cancer rather than on its T category.…”
Section: Treatmentsupporting
confidence: 66%
“…A complex reconstruction is required after a large surgical resection involving the maxillary and/or frontal bone; the maxillary and frontal bones are centerpiece of the middle and upper face, respectively, and their resection has aesthetical, functional (i.e., oculopalpebral, speaking-, and swallowing-related), and vital (i.e., protection of the skull base, intracranial content, and vessels from microbes and desiccation) implications. Moreover, sinonasal malignancies most often require a multimodal management, with a high rate of patients sent for adjuvant treatments, [ 112 , 113 , 114 ] whose toxicity can be amplified in case of suboptimal reconstruction. Reconstruction of midfacial defects created through resection of an SNSCC constitutes a complex and technical challenge, and preoperative planning is paramount [ 115 , 116 ].…”
Section: Treatmentmentioning
confidence: 99%
“…Another example of deepening the understanding of cancer local behavior is the relationship between histologic growth pattern and topographic gross extension. For instance, it has been revealed that perineural and lymphovascular invasion substantially drive local extension of cancers of the maxillary sinus regardless of their histology [47]. In particular, tumors displaying lymphovascular invasion tend to grow with a caudal direction and give nodal metastases, while those with perineural invasion more frequently invade superior, medial, and posterior structures.…”
Section: Future Directions: "Know Your Enemy"mentioning
confidence: 99%
“…While surgery combined with neoadjuvant and adjuvant radiation and chemotherapy has improved the overall outcomes of advanced sinonasal cancers, surgery still remains the principal modality of treatment (39)(40)(41). Clear-margin resection has been proven to significantly impact patient prognosis and can be considered the most important surgeoncontrollable variable (13,(42)(43)(44)(45).…”
Section: Discussionmentioning
confidence: 99%